REVOLUTIONIZING PUBLIC INSTITUTIONS: EXPLORING THE EFFECTS OF DIGITAL HUMAN RESOURCE MANAGEMENT - Carter, Emily (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
In the rapidly evolving landscape of the public sector, human resource management (HRM) is a critical component, and its effective implementation is paramount for the success of public organizations. This study delves into the impact of digital technologies on HRM in the public sector, exploring its transformative potential. The digital age has introduced new opportunities and challenges to HRM practices in public organizations, with web-based technologies facilitating more efficient HR processes. However, the rapid pace of digital transformation also poses potential threats, particularly in areas such as data protection and human-computer collaboration. This paper examines the evolving role of HRM within the public sector, considering its unique complexities in contrast to the private sector. As the public sector adapts to the changing environment, it faces a growing need for agility, innovation, and responsiveness to international competition. The incorporation of HRM concepts and methodologies from the private sector reflects the broader shift towards more competitive and globally oriented public organizations. This paper highlights the multifaceted nature of HRM in the public sector, emphasizing the necessity of HRM strategies that align with the unique goals, values, and services offered by these organizations.